2004
DOI: 10.1148/radiol.2332031800
|View full text |Cite
|
Sign up to set email alerts
|

Integrated FDG PET/CT in Patients with Persistent Ovarian Cancer: Correlation with Histologic Findings

Abstract: Integrated PET/CT depicts persistent ovarian carcinoma with a high positive predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(76 citation statements)
references
References 34 publications
2
64
0
10
Order By: Relevance
“…PET/CT performed better than did CE CT in the detection of paraaortic lymph node involvement. Our results are similar to those of Sironi et al ( 16 ), who reported that PET/CT was better for detecting peritoneal and lymph node metastases than for detecting pelvic local recurrence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PET/CT performed better than did CE CT in the detection of paraaortic lymph node involvement. Our results are similar to those of Sironi et al ( 16 ), who reported that PET/CT was better for detecting peritoneal and lymph node metastases than for detecting pelvic local recurrence.…”
Section: Discussionsupporting
confidence: 91%
“…In the prior studies, researchers found that accuracy, sensitivity, and specifi city were 63%-100%, 73%-100%, and 40%-100%, respectively, at the patient level and 72%-96%, 41%-78%, and 75%-99%, respectively, at the region level ( 14,16,17,20,(25)(26)(27)(28)(29)(30). In these prior studies, the diagnostic The number, size (on CE CT and PET/CT images) and SUV max (on PET/CT images) of peritoneal deposits (for all three readers) and of distant (M1) lymph node metastases (readers 1 and 2 only) were signifi cantly associated with poor survival ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, obtaining histopathologic confirmation is not very common, because the patients are mostly treated with chemotherapy. On the other hand, patients with a positive PET/CT and high CA125 levels had a recurrence of disease more frequently, and therefore (13). Small implants (<5 mm) and low disease volumes are inconsistently recognized, particularly in upper abdomen quadrants including the hepatic dome, epigastrium, and left upper abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Combined PET/CT is more advantageous in terms of spatial resolution than PET, due to a more precise anatomical localization by accompanying CT images. Several reports established the improvement of the diagnostic accuracy of metastatic lymphadenopathies in patients with primary or recurrent ovarian cancer (11,(18)(19)(20)(21). In our study, both the sensitivities of pelvic lymph node and paraaortic lymph node metastases were low for both CT or MRI and 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%